Unveiling the Physics Secrets of Bajiquan: A STEAM-Integrated Teaching Approach - Haidong Chen; Weilei Yang; Jinyong Feng; Jiasheng Lv; Ran Chen (IEEE Access)
A compelling vision is emerging in education - integrating the arts with STEM, forming a holistic approach known as STEAM. Leveraging recent advances in motion analysis technology, this study explores the potential of a STEAM-based pedagogy incorporating the Chinese martial art of Bajiquan to enhance college students’ understanding and application of physics principles. An empirical study was conducted with sophomore university students to investigate the feasibility of this approach. A three-phase intervention utilizing STEAM principles was implemented, focusing on Bajiquan movement practice and analysis, supplemented by instructional videos and images created using motion analysis tools to visualize the underlying physics concepts. These materials highlighted principles such as “Conservation of momentum,” “Linear dynamics,” and “Rotational dynamics” within the context of Bajiquan techniques. Learning interest questionnaires and physics knowledge tests were administered before and after the intervention to assess its impact. One-way repeated measures ANOVA and paired samples t-tests revealed significant improvements in learning interest and physics knowledge scores following the intervention. These findings suggest that integrating Bajiquan and motion analysis within a STEAM framework can promote a deeper understanding of physics concepts and enhance students’ overall engagement with the subject matter.